Toleration : an Elusive Virtue. - Heyd, David (Princeton University Press, 2001)
If we are to understand the concept of toleration in terms of everyday life, we must address a key philosophical and political tension: the call for restraint when encountering apparently wrong beliefs and actions versus the good reasons for interfering with the lives of the subjects of these beliefs and actions. This collection contains original contributions to the ongoing debate on the nature of toleration, including its definition, historical development, justification, and limits. In exploring the issues surrounding toleration, the essays address a variety of provocative questions. Is tol.